Effects of reproductive period duration and number of pregnancies on midlife ECG indices: a secondary analysis from the Women's Health Initiative Clinical Trial. Issue 8 (17th August 2018) - Parikh, Nisha I; Kapphahn, Kristopher; Hedlin, Haley; Olgin, Jeffrey E; Allison, Matthew A; Magnani, Jared W; Ryckman, Kelli R; Waring, Molly E; Perez, Marco Valentin; Howard, Barbara V
Abstract : Objectives: Pregnancy, menses and menopause are related to fluctuations in endogenous sex hormones in women, which cumulatively may alter cardiac electrical conduction. Therefore, we sought to study the association between number of pregnancies and reproductive period duration (RD, time from menarche to menopause) with ECG intervals in the Women's Health Initiative Clinical Trials. Design: Secondary analysis of multicentre clinical trial. Setting: USA. Primary outcome measures: ECGintervals: PR interval, P-wave duration, P-wave dispersion, QTc interval. Participants: n=40 687 women (mean age=62 years) participating in the Women's Health Initiative Clinical Trials. 82.5% were white, 9.3% black, 4% Hispanic and 2.7% Asian. Methods: In primary analysis, we employed multivariable linear regression models relating number of pregnancies and RD with millisecond changes in intervals from enrolment ECG. We studied effect modification by hormone therapy use. Results: Among participants, 5+ live births versus 0 prior pregnancies was associated with a 1.32 ms increase in PR interval (95% CI 0.25 to 2.38), with a graded association with longer QTc interval (ms) (none (prior pregnancy, no live births)=0.66 (–0.56 to 1.88), 1=0.15 (–0.71 to 1.02), 2–4=0.25 (–0.43 to 0.94) and 5+ live births=1.15 (0.33 to 1.98), p=0.008). RD was associated with longer PR interval and maximum P-wave duration (but not P-wave dispersion) among never users of hormone therapy: (PR (ms) per additional RD year: 0.10 (0.04 to 0.16); higher P-wave duration (ms): 0.09 (0.06 to 0.12)). For every year increase in reproductive period, QTc decreased by 0.04 ms (−0.07 to –0.01). Conclusions: An increasing number of live births is related to increased and RD to decreased ventricular repolarisation time. Both grand multiparity and longer RD are related to increased atrial conduction time. Reproductive factors that alter midlife cardiac electrical conduction system remodelling in women may modestly influence cardiovascular disease risk in later life. Trial registration number: NCT00000611; Post-results.